An exploration of contemporary social challenges faced by hijab-wearing women in multi-cultural society of Taraba state: solution from Islamic education / Hamza Manu, Muhammad Zaidi Abdulrahman and Raja Hisyamuddin Raja Sulong - Manu, Hamza; Abdulrahman, Muhammad Zaidi; Raja Sulong, Raja Hisyamuddin (Academy of Contemporary Islamic Studies (ACIS), Universiti Teknologi MARA (UiTM), 2023)
This study explores the contemporary social challenges facing Muslim women in hijab in the multicultural society of Taraba state, Nigeria. The qualitative approach was utilised, employing interviews as the primary instrument for data collection. Twelve (12) informants from academicians, civil servants, scholars, and religious organisations within the state, were interviewed. The data collected were analysed using thematic analysis and theoretical explanations. The study reveals that the influx of Western cultures, the assertion of Western civilization by some Muslims, fashion, and liberalism, have a negative impact on women wearing hijab in the multicultural society of Taraba state, Nigeria. Additionally, Islamaphobia, the influence of social and mainstream media, cultural ceremonies and festivities, and the influence of peer groups are some of the fundamental social challenges against Muslim women in hijab in Taraba state and its surroundings. Thus, the study concluded the existing contemporary social challenges faced by hijab-wearing women are due to Westernisation, fashion, liberalism, Islamaphobia, cultural festivities, negative portrayals in social and mainstream media and the influence of peer groups.